Type D Personality and Big Five Personality Traits and the Risk of Breast Cancer: A Case-Control Study - Wojciechowska, Irena; Matkowski, Rafał; Pawłowski, Tomasz (Frontiers in Psychiatry, 2022)
Objective: The goal of this study is to establish the differences in Type D personality and Big five personality traits between a group of newly diagnosed breast cancer patients and a group of controls. Methods: A comparative study of breast cancer patients and women without previous history of cancer was carried out. We used Type D Scale-14 as an instrument for the assessment of the type-D personality pattern and NEO-FFI for the assessment of the Big Five personality traits. Conditional logistic regression models were used to estimate odds ratios and 95% confidence intervals were applied for breast cancer by personality trait factors. Results: Negative affectivity (NA) (OR = 4.45 95% CI: 1.96 – 10.61), neuroticism HIGH (OR = 3.97, 95% CI: 1.08 – 15.81), openness to experience HIGH (OR = 3.47 95% CI: 1.11 – 11.49), were significantly related to an increased risk of breast cancer, whereas Social Inhibition (SI) was associated with a decreased risk of breast cancer (OR = 0.40 95% CI: 0.16 – 0.92). Conclusions: This was the first case-control study which analyzed NA and SI traits in breast cancer patients. SI as a breast-cancer risk decreasing factor might indicate that expressing negative emotions is not always a healthy mechanism of their regulation.